COVID-19 vaccine hesitancy and confidence in the Philippines and Malaysia: A cross-sectional study of sociodemographic factors and digital health literacy - Ken Brackstone; Roy R. Marzo; Rafidah Bahari; Michael G. Head; Mark E. Patalinghug; Tin T. Su (Public Library of Science (PLoS), 2022)
With the emergence of the highly transmissible Omicron variant, large-scale vaccination coverage is crucial to the national and global pandemic response, especially in populous Southeast Asian countries such as the Philippines and Malaysia where new information is often received digitally. The main aims of this research were to determine levels of hesitancy and confidence in COVID-19 vaccines among general adults in the Philippines and Malaysia, and to identify individual, behavioural, or environmental predictors significantly associated with these outcomes. Data from an internet-based cross-sectional survey of 2558 participants from the Philippines (N = 1002) and Malaysia (N = 1556) were analysed. Results showed that Filipino (56.6%) participants exhibited higher COVID-19 hesitancy than Malaysians (22.9%; p < 0.001). However, there were no significant differences in ratings of confidence between Filipino (45.9%) and Malaysian (49.2%) participants (p = 0.105). Predictors associated with vaccine hesitancy among Filipino participants included women (OR, 1.50, 95% CI, 1.03-1.83; p = 0.030) and rural dwellers (OR, 1.44, 95% CI, 1.07-1.94; p = 0.016). Among Malaysian participants, vaccine hesitancy was associated with women (OR, 1.50, 95% CI, 1.14-1.99; p = 0.004), social media use (OR, 11.76, 95% CI, 5.71-24.19; p < 0.001), and online information-seeking behaviours (OR, 2.48, 95% CI, 1.72-3.58; p < 0.001). Predictors associated with vaccine confidence among Filipino participants included subjective social status (OR, 1.13, 95% CI, 1.54-1.22; p < 0.001), whereas vaccine confidence among Malaysian participants was associated with higher education (OR, 1.30, 95% CI, 1.03-1.66; p < 0.028) and negatively associated with rural dwellers (OR, 0.64, 95% CI, 0.47-0.87; p = 0.005) and online information-seeking behaviours (OR, 0.42, 95% CI, 0.31-0.57; p < 0.001). Efforts should focus on creating effective interventions to decrease vaccination hesitancy, increase confidence, and bolster the uptake of COVID-19 vaccination, particularly in light of the Dengvaxia crisis in the Philippines.